Donor skin allograft survival after bone marrow transplantation: Case report and systematic review of the literature☆. Issue 1 (January 2019) - Nunez-Villaveiran, Teresa; Feasel, Patrick; Keenan, Sean; Aliotta, Rachel; Bosler, David; Stearns, Duncan; Bergfeld, Wilma; Gurunluoglu, Raffi
Abstract: Background: We present a case of skin allograft survival in a patient who previously received a bone marrow transplant from the same HLA-matched donor. DNA fingerprinting of skin biopsies showed mixed cellularity originating from the donor and recipient (68% and 32% donor DNA in the allograft skin and the native recipient's skin, respectively). Histologic sections demonstrated both grade 3/4 rejection and graft-versus-host-disease. We have conducted a systematic review in search for other cases of donor skin allograft survival after a bone marrow or hematopoietic stem cell transplantation. Methods: All reported cases in English, Spanish, French, and German were captured using the electronic databases. Bibliographies of relevant articles were manually searched. Results: Nineteen patients (12 females) who received skin allografts from their bone marrow or hematopoietic stem cell donors were identified. Average age was 27.2 years (range: 5 months to 64 years). Skin allografts were used to treat graft-versus-host-disease, Herlitz junctional epidermolysis bullosa, and to test tolerance before a kidney transplantation from the same donor. Eight cases were not receiving immunosuppressive therapy. Allografts survived in all patients. In three patients, skin punch biopsies were taken, and these biopsies demonstrated mixed donor and recipient cellularity. The pathology result is specified in two more cases, with no signs of rejection. Conclusions: The same donor skin allografts may be a safe option to treat severe cutaneous conditions in recipients of a bone marrow/hematopoietic stem cell transplantation. However, future studies are needed to confirm these results.